Investigating connections between teacher identity and pedagogy in a content-based classroom. (August 2021) - Kessler, Matt
Abstract: Though much scholarship has investigated the nexus of language teachers' identities and classroom pedagogies, such studies often have focused on novice teachers in training or experienced practitioners who are working within university IEP or EAP program contexts. Crucially, little scholarship has examined contexts involving content-based instruction (CBI), where many times, instructors are not linguistically trained yet may adopt discipline-specific practices and/or develop their own unique methods for teaching L2 learners. The current study explores this gap, examining a CBI instructor of a legal research and writing course in an L2 English legal education program (i.e., LLM program). For 16 weeks, the researcher conducted a classroom-based ethnography to investigate how an experienced law instructor's various role identities impacted his pedagogical practices as he taught LLM students to write a legal genre called the office memorandum. Data consisted of: in-class observations, fieldnotes, artifacts (e.g., syllabi, assignments), semi-structured interviews, and a visualization reflection. The findings illustrate how three primary role identities shaped the instructor's pedagogy in ways that permeated his curriculum design and his manner of lesson presentation. Implications for L2 educators and researchers are discussed.